Impact measurement of value-based intermediation among Malaysian Islamic financial institutions / Engku Zaidah Engku Abdul Rahman … [et al.] - Engku Abdul Rahman, Engku Zaidah; Ismail, Rina Fadhilah; Zainon, Saunah; Adhariani, Desi (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2022)
There are still insufficient data concerning the impacts of Value-based Intermediation (VBI) performance output on sustainability although the Global Alliance for Banking on Values has been used to measure VBI performance of Islamic Financial Institutions (IFIs). Therefore, this study aimed to measure the impacts of VBI adoption among IFIs in Malaysia using the logic model approach. Data were extracted from IFIs’ annual reports published and the Association of Islamic Banking Institution Malaysia (AIBIM)’s report on VBI Implementation issued from 2017 to 2020. The results showed that VBI performance measures were different among Community of Practices (CoPs) according to their different levels of adoption. The levels of VBI adoption were more likely to persistently affect customers, communities, and the environment. The logic model approach clarified that VBI performance reports should not be one-fit-all as the adoption level varied among CoPs. The findings also indicated that VBI performance information in the CoPs’ annual reports might engage them with targeted customers, communities, and the environment, expecting to add new insights into the literature on performance measurement in the area of Islamic Finance. This could assist regulators and industry players in planning more strategic initiatives and provide clear guidelines for VBI adoption.